Experiencing (from) the inside – Mediated perspectives in kindergartens - Bråten, Ingvard; Hoem, Jon Øivind (FormAkademisk, 2021)
This paper presents a case study of preservice kindergarten teachers’ use of new form of digital imagery. The paper introduces spherical cameras and digital microscopes and discusses their affordances when introduced in practical use in in teacher education and in kindergartens. The use in kindergartens was introduced through a class of 34 teacher students in kindergarten education. The students were specializing in Arts and design at Western Norway University of Applied Sciences. The use of images from spherical cameras and digital microscopes is discussed and analysed, based on data from student responses through two questionnaires, group presentations and discussions in class, and an analysis of various media material produced by students.